Economic Feasibility of Five Year Old Melia dubia in Different Planting Densities - Thakur, N. S.; Chauhan, R. S.; Hegde, H. T.; Singh, Narendra; Kumar, Ashok; Gunaga, R. P.; Bhuva, D. C. (Indian Forester, 2023)
This study was conducted to ascertain the economic feasibility of Melia dubia planted under different planting densities viz. (i) 2500 trees ha-1 (2x2 m), (ii) 1666 trees ha-1 (3x2 m), (iii) 1111 trees ha-1 (3x3 m) and (iv) 1250 trees ha-1 (4x2 m ), at the age of 5 years. The maximum net returns (at the age of 5 years) amounting to ₹752791 were gained from 2x2 m planting spacing with 2500 trees ha-1 . The per year net returns were in the order of 2500 trees ha-1 (2x2 m), >1666 trees ha-1 (3x2 m) >1250 trees ha-1 (4x2 m) >1111 trees ha-1 (3x3 m) with respective amounts of ₠150558>119780>99794 3x2 m>2x2 m>3x3 with respective values as 3.35>3.23>2.87>2.45. The net present value (NPV), at 5 years, was maximum (` 553278) for 2x2 m spacing followed by ₹444374, 371153 and 313230 from 3x2, 4x2 and 3x3 m spatial geometry. Although, NPV was maximum from 2x2 m planting spacing, nonetheless, internal rate of return (IRR) was highest from 4x2 m followed by 3x2, 2x2 and 3x3 m spatial geometry.